PENGARUH KONSENTRASI SEMEN TERHADAP SIFAT FISIK DAN MEKANIK PAPAN SEMEN PARTIKEL DARI KAYU SENGON (Paraserianthes falcataria) - Dwi Hariyati; Gusti Abdul Rahmat Thamrin; Zainal Abidin (Universitas Lambung Mangkurat, 2020)
The aim of this research is to analyze the effect of cement concentration on the physical and mechanical properties of the cement particle board of sengon wood powder (Paraserianthes falcataria). Analyzing the suitability of wood as raw material for cement boards. The physical properties of the particle cement board with the addition of a cement ratio of 225 grams per treatment did not significantly affect the value of the water content. Overall average water content reaches less than 14% that meets SNI, the average value of density produced has a very significant effect but only on treatment with a ratio of powder: 3: 1 cement that meets the Indonesian National Standard (SNI) with SNI requirements for cement board density from 0.4 to 0.9 gr / cm3 (low density), the average modulus of elasticity (MoE) produced significantly influences and fulfills SNI for cement board particles 2.55 kgf / cm2 at A2 treatment, A3 and A4 but have not met the standard in A1 treatment, the average value of fracture firmness (MoR) for each treatment has a very significant effect and according to the standards stipulated SNI min 133 kgf / cm2 it meets the standard in A4 treatment with a ratio between powder and cement 6 : 1 while not meeting the standards in A1, A2 and A3 treatments. The suitability of Sengon wood powder (Paraserianthes falcataria) to the physical and mechanical properties of particle cement board in the form of water content, density, flexural strength (MoE) and fracture firmness (MoR) for each given treatment is appropriate because most have met Indonesian National Standard (SNI).Keywords: Cement Board, Physical and Mechanical Properties of Cement Board, Particle Board